Current and Future Pathotyping Platforms for Plasmodiophora brassicae in Canada - Heather H. Tso; Leonardo Galindo-González; Stephen E. Strelkov (Plants, 2021)
Clubroot, caused by Plasmodiophora brassicae, is one of the most detrimental threats to crucifers worldwide and has emerged as an important disease of canola (Brassica napus) in Canada. At present, pathotypes are distinguished phenotypically by their virulence patterns on host differential sets, including the systems of Williams, Somé et al., the European Clubroot Differential set, and most recently the Canadian Clubroot Differential set and the Sinitic Clubroot Differential set. Although these are frequently used because of their simplicity of application, they are time-consuming, labor-intensive, and can lack sensitivity. Early, preventative pathotype detection is imperative to maximize productivity and promote sustainable crop production. The decreased turnaround time and increased sensitivity and specificity of genotypic pathotyping will be valuable for the development of integrated clubroot management plans, and interest in molecular techniques to complement phenotypic methods is increasing. This review provides a synopsis of current and future molecular pathotyping platforms for P. brassicae and aims to provide information on techniques that may be most suitable for the development of rapid, reliable, and cost-effective pathotyping assays.